Managing the Transition to a Circular Economy Action Plans in the Tourism Sector - Marival Segarra (SpringerBriefs in Business, 2024)
This open-access volume offers a thorough, interdisciplinary exploration of how the tourism sector can transition to a circular economy. Aimed at researchers, policymakers, and industry stakeholders, it provides both theoretical insights and practical action plans, focusing on sustainability in the tourism industry